Petrophysical interpretation of Euphrates Formation in Ajil Oil Field, Salah Al-Deen Governorate, Central Iraq - Alkhaykanee, Mustafa H.; Al-Dulaimi, Salam I. (Iraqi Journal of Science, 2019)
The study intends to well logs interpretation to determine the petrophysical parameters of Euphrates Formations in Ajeel Oil Field. The petrophysical properties have been determined from well logging, Euphrates Formation in terms of reservoirs units, consist of two Petrophysical properties. Total porosity, effect porosity and secondary porosity have been calculated from neutron, density, and sonic logs. secondary porosity is high and it's resulted from diagenesis processes in the formation. From RHOB-NPHI and N/M cross plot, Euphrates Formation composed mainly from Limestone and dolomite with nodules of anhydrite. Dhiban Formation composed mainly of anhydrite, so it's represented the cap rocks for Euphrates Reservoir were recognized based on the reading of GR, RHOB, NPHI, and DT logs. These rocks composed mainly from Anhydrite and anhydritic limestone. Hydrocarbone saturation include both gas and oil, where Ajeel oil field is production oil and gas.